2022
DOI: 10.55230/mabjournal.v51i2.2164
|View full text |Cite
|
Sign up to set email alerts
|

CONSUMPTION OF Hibiscus sabdariffa DRIED CALYX ETHANOL EXTRACT IMPROVED REDOX IMBALANCE AND GLUCOSE PLASMA IN VITAMIN B12 RESTRICTION DIET IN RATS

Abstract: This study aimed to evaluate the effect of Hibiscus sabdariffa L. dried calyx ethanolic (HSE) extract on the redox imbalance and glucose plasma of vitamin B12 restriction Sprague-Dawley rats. The rat was fed a Vitamin B12 Restriction Diet for 16 weeks and treated with HSE as the treatment group. One group was fed a restriction diet not treated with HSE as a positive control group, and another was fed a control chow diet not treated with HSE as a negative control group. Vitamin B12, MDA, SOD activity enzyme, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…We previously demonstrated that the dietary restriction of vitamin B12 causes oxidative stress, which is a state of cellular imbalance between free radicals and antioxidants, via the formation of homocysteine. The amino acid homocysteine, as previously studied, can cause oxidative stress by increasing the production of hydroxyl radicals [ 18 ]. Fats, proteins, carbohydrates and nucleic acids can all be oxidized by this radical group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We previously demonstrated that the dietary restriction of vitamin B12 causes oxidative stress, which is a state of cellular imbalance between free radicals and antioxidants, via the formation of homocysteine. The amino acid homocysteine, as previously studied, can cause oxidative stress by increasing the production of hydroxyl radicals [ 18 ]. Fats, proteins, carbohydrates and nucleic acids can all be oxidized by this radical group.…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that the roselle extracts improved the antioxidant defense against oxidative stress via the NRF2 signaling pathway. Previous research has demonstrated that rosella extract in the liver of vitamin B12-treated rats reduces lipid peroxidation production, and increases levels of antioxidant enzymes such as SOD [ 18 ]. In this study, the vitamin B12-restricted group supplemented with rosella extract expressed higher liver NRF2 levels than the group without rosella extract.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation